2001
DOI: 10.1006/bijl.2001.0537
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the global species richness of an incompletely described taxon: an example using parasitoid wasps (Hymenoptera: Braconidae)

Abstract: The need to estimate the magnitude of undescribed species richness arises from the limited resources available to the description and conservation of biodiversity, the continuous loss of diversity that we are currently experiencing, and the sheer scale of the task of accurate measurement. Several estimation methods have previously been described and discussed in some detail, but the reliability of these methods is difficult to assess. In this study, we use two independent methods to predict the global species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 14 publications
3
36
0
1
Order By: Relevance
“…Homoterpene (E)-4,8-dimethyl-1,3,7-nonatriene and other terpenes seemed to be important cues for orientation of C. plutellae to P. xylostella-damaged plants (Shiojiri et al 2001). Therefore, C. plutellae and other Braconids at the top of the food chains maintain important position in terms of global biodiversity (Dolphin and Quicke 2001). Soler et al (2005) showed that C. glomerata, parasitoid of caterpillars of the cabbage butterfly Pieris brassicae, developed significantly slower and adults were smaller when roots of Brassica nigra (Brassicaceae) plants were damaged by larvae of the cabbage root fly, Delia radicum (Diptera: Anthomyiidae).…”
Section: B Oleraceamentioning
confidence: 99%
“…Homoterpene (E)-4,8-dimethyl-1,3,7-nonatriene and other terpenes seemed to be important cues for orientation of C. plutellae to P. xylostella-damaged plants (Shiojiri et al 2001). Therefore, C. plutellae and other Braconids at the top of the food chains maintain important position in terms of global biodiversity (Dolphin and Quicke 2001). Soler et al (2005) showed that C. glomerata, parasitoid of caterpillars of the cabbage butterfly Pieris brassicae, developed significantly slower and adults were smaller when roots of Brassica nigra (Brassicaceae) plants were damaged by larvae of the cabbage root fly, Delia radicum (Diptera: Anthomyiidae).…”
Section: B Oleraceamentioning
confidence: 99%
“…A medium-term alternative might be to try and make some broad estimates of asymptotic species richness using established extrapolation techniques. A number of methods are available to do this (see O'Brien & Wibmer, 1979;Palmer, 1990;Colwell & Coddington, 1994;Hammond, 1994;Williams & Gaston, 1994;Dolphin & Quicke, 2001). This will undoubtedly be a time-consuming process, but is not beyond the means of a dedicated army of researchers, and some progress has already been made (see Bartlett et al, 1999;Dolphin & Quicke, 2001).…”
Section: (C ) Extant Species Richnessmentioning
confidence: 99%
“…A number of methods are available to do this (see O'Brien & Wibmer, 1979;Palmer, 1990;Colwell & Coddington, 1994;Hammond, 1994;Williams & Gaston, 1994;Dolphin & Quicke, 2001). This will undoubtedly be a time-consuming process, but is not beyond the means of a dedicated army of researchers, and some progress has already been made (see Bartlett et al, 1999;Dolphin & Quicke, 2001). However, for some taxa, such as Coleoptera, extrapolation via some common techniques may not yet be reliably performed because the accumulation curve of species has not yet begun to asymptote strongly (Gaston, 1991).…”
Section: (C ) Extant Species Richnessmentioning
confidence: 99%
“…Here I explore latitudinal trends in the species richness of genera, body size and biology of the described members of the Ichneumonidae and of its sister family, the Braconidae, with approximately 24000 and 17000 described species respectively [20], [21], [22]. For both families there are significant increases in the proportions of idiobiont ectoparasitoid species towards the equator as predicted by, for example, the nasty host hypothesis.…”
Section: Introductionmentioning
confidence: 99%